Effectiveness of climate change e-module based on SSI-TL to improve problem-solving skills and environmental literacy - Moh. Usamah; Fatchur Rohman; Mimien Henie Irawati Al Muhdhar; Sarah Abdul Razaq (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: The development of problem-solving skills and environmental literacy is a priority in climate change education. Socio-scientific issues-based learning supported by digital modules is considered relevant for linking scientific concepts with value reflection and contextual decision-making. However, empirical studies examining the effectiveness of integrating both approaches to simultaneously enhance these competencies remain limited. Objectives: This study aimed to examine the effectiveness of a climate change e-module based on Socio-Scientific Issues Teaching and Learning (SSI-TL) in improving students’ problem-solving skills and environmental literacy. Methods: A quasi-experimental non-equivalent control group pretest–posttest design was employed. The study involved 70 tenth-grade students at SMAN 8 Malang, who were divided into an experimental group and a control group. Improvement was analyzed using Normalized Gain (N-Gain), followed by Analysis of Covariance (ANCOVA) to test differences between groups. Results: The N-gain results indicated medium improvement in both variables, with higher scores in the experimental group compared to the control group. ANCOVA confirmed that the differences were statistically significant (p < 0.001). Conclusion: The integration of structured SSI-TL syntax within an e-module enhances scientific reasoning, value reflection, and environmental action orientation. The findings provide conceptual and practical support for developing digital learning resources in climate change education.